2019
DOI: 10.1172/jci.insight.124588
|View full text |Cite
|
Sign up to set email alerts
|

Human antibody response to Zika targets type-specific quaternary structure epitopes

Abstract: Conflict of interest: MHC, HT, BDM, SAD, and AMDS are co-inventors on a patent application (US 62589006, filed 11/21/2017) describing the discovery and use of A9E and G9E human mAbs. BD and ED are employees of Integral Molecular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 83 publications
(113 reference statements)
4
72
0
Order By: Relevance
“…We conclude that the rE M antigen induces an EDIII focused antibody response that is poorly neutralizing, whereas rE D antigens stimulate robust neutralizing antibody responses that target epitopes distinct from simple EDIII epitopes. We recently isolated two ZIKV-specific strongly neutralizing human mAbs (A9E and G9E) from a person who was infected with ZIKV in 2016 23 . These antibodies map to complex epitopes on domain I (A9E) and domain II (G9E) of ZIKV E protein 23 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We conclude that the rE M antigen induces an EDIII focused antibody response that is poorly neutralizing, whereas rE D antigens stimulate robust neutralizing antibody responses that target epitopes distinct from simple EDIII epitopes. We recently isolated two ZIKV-specific strongly neutralizing human mAbs (A9E and G9E) from a person who was infected with ZIKV in 2016 23 . These antibodies map to complex epitopes on domain I (A9E) and domain II (G9E) of ZIKV E protein 23 .…”
Section: Resultsmentioning
confidence: 99%
“…We recently isolated two ZIKV-specific strongly neutralizing human mAbs (A9E and G9E) from a person who was infected with ZIKV in 2016 23 . These antibodies map to complex epitopes on domain I (A9E) and domain II (G9E) of ZIKV E protein 23 . Moreover, antibody blockade assays using these mAbs and human immune sera indicated that the epitopes targeted by these mAbs also are targeted by antibodies in immune serum from Zika patients but not dengue patients 23 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further test the native antigenicity of ZIKV RVPs, we performed an ELISA with RVPs using various conformational MAbs. As detection MAbs, we used two EDE MAbs (C8 and C10) and five neutralizing anti-ZIKV MAbs (ZIKV-117, ZIKV-195, ZIKV-116 (29), A9E (28), and LM-081). Each of these seven MAbs represents a distinct conformational region on the native structure of ZIKV prM/E ( Fig.…”
Section: Zikv Rvps Are Infectious and Antigenically Identical To Livementioning
confidence: 99%